2014
DOI: 10.7763/ijmlc.2014.v4.439
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Face and Fingerprint for Robust Personal Verification System

Abstract: Abstract-Personal verification system that uses a single biometric trait often faces numerous limitations such as noisy sensor data, non-universality, non-distinctiveness and spoof attack. These limitations can be overcome by multimodal biometric systems that consolidate the evidence presented by multiple biometric sources and typically has better recognition performance compared to systems based on a single biometric modality. This study proposes fusion of face and fingerprint for robust recognition system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Chaudhary, and Sheetal, et al [10] FpVTE 2003 was analysis to performance and calculated the efficiency of proposed method, fingerprint verification and identification systems. Its summary and analysis report Meva et al, [11] and NIST Biometric and Evaluation and Development paper by Hassan, Norsalina, and Dzati Athiar Ramli et al, [12], Dandawate, and Yogesh H et al [13] and W. Yang, integrated information presented by two fingers at the match score level by probability proportion calculated nonparametric statistical estimates. It was found that multiple fingers improve the verification performance by 4%.…”
Section: \ Fig1 Block Diagram For Multimodal Fusion Methodsmentioning
confidence: 99%
“…Chaudhary, and Sheetal, et al [10] FpVTE 2003 was analysis to performance and calculated the efficiency of proposed method, fingerprint verification and identification systems. Its summary and analysis report Meva et al, [11] and NIST Biometric and Evaluation and Development paper by Hassan, Norsalina, and Dzati Athiar Ramli et al, [12], Dandawate, and Yogesh H et al [13] and W. Yang, integrated information presented by two fingers at the match score level by probability proportion calculated nonparametric statistical estimates. It was found that multiple fingers improve the verification performance by 4%.…”
Section: \ Fig1 Block Diagram For Multimodal Fusion Methodsmentioning
confidence: 99%
“…were 310, 301, 290, 283, 271 lx, respectively. For evaluating the verification accuracy, the following values: GAR, FRR, FAR, and ERR [34] were calculated in percentage from the experimental results and shown in Table 4. Note that GAR and ERR are calculated from 1 -FRR, and an average of FRR and FAR, respectively.…”
Section: Performancementioning
confidence: 99%
“…Fusing occurs following the fusion of personal features after matching fusion. This comprises the following fusion levels: rank level fusion, match decision level fusion, and score level fusion that can gives good accuracy between 92 and 96%, for more information details you can find it in [9][10][11][12][13][14][15][16][17].…”
Section: Related Wordmentioning
confidence: 99%